Banking in the Digital Age: How Technology, Capital, and Risk Shape Profitability - Hidayatullah, Indra; Sumiati (Jurnal Management Risiko dan Keuangan, 2025)
Bank profitability, as a key indicator of financial performance, has exhibited varying trends during the period from 2019 to 2024. Digital transformation presents opportunities for banks to enhance efficiency and profitability; however, challenges related to capitalization and credit risk remain primary concerns for regulators and industry participants in maintaining long-term stability and profitability. This explanatory quantitative study aims to analyze the influence of digital transformation, capitalization, and credit risk on profitability. The objects of this study are banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. Using a census or saturated sampling method, 16 banks out of a total of 47 were selected as the sample. The study employs descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, and hypothesis testing, all conducted using SPSS version 27. The results of the analysis indicate that digital transformation does not have a significant effect on profitability, while capitalization and credit risk significantly influence profitability. Therefore, banks need to strengthen their digital capabilities and risk management while optimizing their capital structure to enhance performance and competitiveness in line with the resource-based view approach.